UKRAINIAN RETAIL MARKET: MAIN DEVELOPMENT TRENDS - Солтис-Шолудько, Наталія (Modern engineering and innovative technologies, 2023)
The theoretical aspects of the essence of the concept of "retail trade" are presented. The current state of trade in Ukraine during 2017–2021 was analyzed. The main indicators were used for the analysis, namely: the number of economic entities on the mar